MARGINALISASI PEREMPUAN DALAM BERITA ONLINE INDONESIA (ANALISIS WACANA KRITIS SARA MILLS) - Neng Windi Agustina Dewi; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Discourse analysis is a method used to uncover the meaning and communication messages present in a text, both in its textual and contextual aspects. This means that the meaning of a text or communication message cannot solely be derived from the explicit written text. Sara Mills' discourse model focuses on discourses about feminism, emphasizing the positions of subjects and objects within the text. Feminist discourse highlights how a text represents women. In reality, women are often portrayed as inferior and in the wrong compared to men in texts. The approach used in this analysis is Sara Mills' discourse approach. The author examines a discourse for analysis titled "Sad Case: 9 Children Raped, Main Perpetrator Still Underage" from Detik.com. The results of the discussion indicate that the author portrays women as objects depicted in news stories. However, on detik.com news, women are also positioned as subjects with the opportunity to narrate events they have experienced from the beginning to the aftermath of rape. In feminist discourse, women are often depicted not as subjects but as objects in many news texts. In this case, women are objectified, and their positions are often defined as mere storytelling materials, victims of abuse, or rape victims, unable to represent themselves. Through the analysis conducted on detik.com media, women are portrayed as victims of rape. The news presented on detik.com depicts women more as a vulnerable group, while men are shown to hold power, rendering the victims powerless. Consequently, when represented in news texts, women are placed in a marginalized position. Keywords: Discourse analysis, Sara Mills approach, feminist discourse.